KEEFEKTIFAN MODEL PEMBELAJARAN GUIDED INQUIRY BERNUANSA KONTEKSTUAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK MATERI SEGIEMPAT KELAS VII - Hidayatun Nikhlah (Universitas Muhammadiyah Semarang, 2017)
This research is motivated by low grade mathematics grade VII and learning completeness not yet as desired. Many factors affect the value of learning achievement, such as low motivation, learner activity is still less so that learning is still centered by the teacher. One attempt to solve the problem is to try to apply the Guided Inquiry model Contextual Nuances. The purpose of the study: (1) To know the use of contextual guided inquiry learning model can achieve the value of students' learning achievement; (2) to know the influence of motivation and activeness to student learning achievement; (3) Knowing the learning achievement of learners using guided inquiry model of contextual nuance is better than expository learning model. This type of research is quasi experiment, with research population of all classes VII MTs. Asy-syarifiyah tahun2016 / 2017.. The sample in this study class VII A as experimental class, control class that is VII B, and as a class of test that is class VII C. Motivation and Activeness as independent variable, while learning achievement as dependent variable. Data collection techniques in this study are: interviews, documentation, tests, observations, and questionnaires. Results of research: that the percentage of learners who achieve learning achievement KKM by 85%. Motivation affects the learning achievement of 82.8% and the remaining 17.2% is influenced by other factors. Analysis of influence test, showed that activeness influence achievement learn equal to 73,5% result of test analysis influence of motivation and activeness to achievement learn is equal to process 83,3%. The average learning achievement of the experimental class is 76 and the control class is 72 It can be concluded that the learning achievement of learners with the Guided Inquiry model of contextual nuance is better than with expository learning. So that learning with Guided Inquiry model of contextual nuance can be said to be effective. Keywords: Guided Inquiry, Contextual, Learning Achievement